Connecting genebanks to farmers in East Africa through the distribution of vegetable seed kits. Issue 3 (15th February 2019) - Stoilova, Tsvetelina; van Zonneveld, Maarten; Roothaert, Ralph; Schreinemachers, Pepijn
Abstract: Genebanks explore new partnerships with farmers and other user groups to provide smallholder farmers in Africa better access to crop diversity for improved nutrition, climate change adaptation and agricultural diversification. This paper shows how the World Vegetable Center (WorldVeg) genebank of traditional African vegetables and its partners distributed over 42, 000 seed kits containing over 183, 000 vegetable seed samples from 2013 to 2017 to smallholder farmers in Tanzania, Kenya and Uganda. The seed kits contained seed samples of promising accessions and open-pollinated breeding lines of traditional African vegetables, and to a lower degree of tomato, Capsicum pepper and soybean, usually enough to plant in a home garden. We identified four research questions to better understand the role of vegetable seed kits in strengthening local seed systems, impact on local vegetable diversity, improving human nutrition and supporting climate-resilient agriculture. As formal seed systems expand their reach, the genebank's role to supply vegetable diversity to public and private breeding programmes becomes more important. To optimize supply of vegetable diversity, the WorldVeg genebank of traditional African vegetables continues working with partners in both formal and local seed systems.